Development under the surface– unintended consequences of settler institutions in Southern Rhodesia, 1896-1962 - Martin Andersson; Erik Green (African Economic History Network (AEHN), 2014)
According to the debate on the long-term impact of colonialism, the central concern is the institutions the colonial powers imposed on the colonies. The main line of argument in this paradigm is that such institutions, once jelled, persisted and provide explanations to current-day development success or failure. While this 'from above' perspective might be natural and reflect the fact that colonial powers indeed are alien rulers declaring supremacy imposing a layer of arrangements for governing the society, the analysis is nevertheless often partial. What this debate misses is that institutions might create a multitude of social forces, some of them perhaps in opposing directions and development dynamics might come about in an unexpected manner. The aim of this paper is to take the case of Southern Rhodesia (c. 1900-1962) – a typical African settler economy - to further add to this discussion by shedding light on a largely discounted economic phenomenon taking place in the rural economy, namely the rise of commercially oriented Africans, in the study epitomized by the Native Purchase Area farmers, that expanded their market activities by intensified use of land and labour. We argue that the relative success of this group largely could be understood as an unintended consequence of settler-oriented colonial institutions.
Keywords: 330